2015
DOI: 10.1007/s10577-015-9492-6
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal distribution and evolution of abundant retrotransposons in plants: gypsy elements in diploid and polyploid Brachiaria forage grasses

Abstract: Like other eukaryotes, the nuclear genome of plants consists of DNA with a small proportion of low-copy DNA (genes and regulatory sequences) and very abundant DNA sequence motifs that are repeated thousands up to millions of times in the genomes including transposable elements (TEs) and satellite DNA. Retrotransposons, one class of TEs, are sequences that amplify via an RNA intermediate and reinsert into the genome, are often the major fraction of a genome. Here, we put research on retrotransposons into the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 60 publications
6
41
0
Order By: Relevance
“…Coffee unigenes were compared against transposable elements sequences available at Repbase protein transposable elements database [36] using a strategy similar to that reported by Santos et al [37] and Marcon et al [38]. Unigenes were considered related to TEs when there was a minimum alignment of 200 bp, a score greater than 200 and a 1e-10 evalue in BlastN.…”
Section: Methodsmentioning
confidence: 99%
“…Coffee unigenes were compared against transposable elements sequences available at Repbase protein transposable elements database [36] using a strategy similar to that reported by Santos et al [37] and Marcon et al [38]. Unigenes were considered related to TEs when there was a minimum alignment of 200 bp, a score greater than 200 and a 1e-10 evalue in BlastN.…”
Section: Methodsmentioning
confidence: 99%
“…It must be emphasized that these authors have also indicated the occurrence of differences between accessions, which has been attributed to structural changes or possible hybridization between different accessions of the species. Repetitive CRM sequences have also been studied in chromosomes of Brachiaria species by Santos et al (2015). This class of retrotransposons is typical of centromeres in grass species, however, there are several CR derivations already identified in species such as barley, wheat, rye, and rice (Presting et al, 1998).…”
Section: Location Of Repetitive Sequences Of Chromosomes In Brachiarimentioning
confidence: 99%
“…B. brizantha and B. decumbens probably have a more abundant, distinct CR responsible for the organization of the centromere. Repetitive CRM sequences have also been studied in chromosomes of Brachiaria species by Santos et al (2015). Discrete signals have been found in the pericentromeric-interstitial region in diploids of B. ruziziensis and B. brizantha.…”
Section: Location Of Repetitive Sequences Of Chromosomes In Brachiarimentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes this mark extended up to the chromosomal arms in the species and hybrids assessed in the current study. According to study of Santos et al (2015) the chromosomal distribution and evolution of gypsy elements (retrotransposons) in diploid and polyploid Brachiaria species are preferably integrated into proximal chromosome regions.…”
Section: Discussionmentioning
confidence: 99%